PENERAPAN STRATEGI MATHEMATICAL INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS XI MIPA SMAN 16 PEKANBARU - Vivi Sitta Savitry (Universitas Negeri Medan, 2021)
Abstract: Application of Mathematical Investigation Strategy to Improve Mathematics Learning Outcomes of Class XI MIPA Students at SMAN 16 Pekanbaru. The specific objectives of this research can be detailed as follows: To determine student learning outcomes using the Mathematical Investigation Strategy learning model. To find out whether there are differences in student learning outcomes using the Mathematical Investigation Strategy learning model with conventional learning models.The formulation of the problem in this study is as follows: Are there differences in student learning outcomes using the Mathematical Inestigation Strategy learning model with conventional learning models? Are student learning outcomes using the Mathematical Instigation Strategy learning model better than student learning outcomes using conventional learning models? The research subject is Class XI MIPA SMA 16 Pekanbaru 2019 as many as 64 students or two classes XI MIPA. student learning in mathematics learning using the Mathematical Investigation Strategy learning model is greater than the student learning outcomes in mathematics learning that do not use the Mathematical Investigation Strategy learning model.Keywords: mathematics, learning outcomes, mathematical investigation strategies Abstrak: Penerapan Strategi Mathematical Investigation Untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas XI Mipa SMAN 16 Pekanbaru.Tujuan khusus dilaksanakannya penelitian ini dapat dirinci sebagai berikut: Untuk mengetahui hasil belajar siswa yang menggunakan model pembelajaran Strategi Mathematical Investigation. Untuk mengetahui apakah terdapat perbedaan hasil belajar siswa yang menggunakan model pembelajaran Strategi Mathematical Investigation dengan model pembelajaran konvensional. Rumusan masalah dalam penelitian ini sebagai berikut: Apakah terdapat perbedaan hasil belajar siswa yang menggunakan model pembelajaran Strategi Mathematical Inestigation dengan model pembelajaran konvensional? Apakah hasil belajar siswa yang menggunakan model pembelajaran Strategi Mathematical Inestigation lebih baik daripada hasil belajar siswa yang menggunakan model pembelajaran konvensional?Subjek penelitian adalah Kelas XI MIPA SMA 16 Pekanbaru 2019 sebanyak 64 anak didik atau dua kelasXI MIPA.Berdasarkan hasil penelitian dapat diketahui bahwa nilai hasil belajar siswa pada pembelajaran matematika dengan menggunakan model pembelajaran Strategi Mathematical Investigation lebih besar daripada nilai hasil belajar siswa pada pembelajaran matematika yang tidak menggunakan model pembelajaran Strategi Mathematical Investigation. Kata Kunci: matematika, hasil belajar, strategi mathematical investigation